2022
DOI: 10.3390/cancers14205032
|View full text |Cite|
|
Sign up to set email alerts
|

Radiotherapy-Related Gene Signature in Prostate Cancer

Abstract: Radiotherapy for localized prostate cancer has increased the cure and survival rates of patients. Besides its local tumoricidal effects, ionizing radiation has been linked to mechanisms leading to systemic immune activation, a phenomenon called the abscopal effect. In this study, we performed gene expression analysis on peripheral blood from prostate cancer patients obtained post- radiotherapy and showed that 6 genes, including CCR7, FCGR2B, BTLA, CD6, CD3D, and CD3E, were down-regulated by a range of 1.5–2.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…FCGR2B is involved in various immune pathways that promote tumor. [ 37 ] Our research found that FCGR2B is closely related to immune-related functions, such as T cell activation and lymphocyte mediated immunity. GSEA analysis showed that in the high expression group of FCGR2B, the biological functions related to cell adhesion molecules (CAMS) and Hematopoietic cell lineage or immune related biological functions mediated by them and JAK-STAT signal pathway were activated.…”
Section: Discussionmentioning
confidence: 91%
“…FCGR2B is involved in various immune pathways that promote tumor. [ 37 ] Our research found that FCGR2B is closely related to immune-related functions, such as T cell activation and lymphocyte mediated immunity. GSEA analysis showed that in the high expression group of FCGR2B, the biological functions related to cell adhesion molecules (CAMS) and Hematopoietic cell lineage or immune related biological functions mediated by them and JAK-STAT signal pathway were activated.…”
Section: Discussionmentioning
confidence: 91%
“…Gene expression analysis of the RNA samples derived from the peripheral blood of PCa patients using next-generation sequencing (NGS) identified a radiotherapy-induced downregulation of a six-gene signature consisting of CCR7, FCGR2B, BTLA, CD6, CD3D, and CD3E [41]. Given that low mRNA expression levels of the gene signature in prostate tumor tissue were correlated with a better 5-year prognosis, this could hold a potent predictive value, which remains to be confirmed by further exploiting the biobanked material.…”
Section: Exploitation Of the Stored Biomaterial: The Clinical Implica...mentioning
confidence: 99%
“…This has led to the development of the radiation sensitivity index, a tool used to predict a patient's response to radiation therapy. It is based on the idea that tumors with certain genetic or molecular characteristics may be more sensitive to radiation therapy [3,4]. Therefore, by analyzing these characteristics, it may be possible to predict which PCa patients will respond well to radiation therapy and have a better recurrence free survival [5].…”
Section: Introductionmentioning
confidence: 99%